Disclosing Pharmacogenetic Feedback of Caffeine via eHealth Channels, Assessment of the Methods and Effects to Behavior Change: A Pilot Study - Alev, Kerti; Kütt, Andres; Viigimaa, Margus (Frontiers in Digital Health, 2021)
Background: The integration of genetic testing into eHealth applications holds great promise for the personalization of disease prevention guidelines. However, relatively little is known about the impact on an individual’s behavior of eHealth applications. Aim: The aim of the pilot study was to investigate the effect of the personalized eHealth application approach to behavior change in a one-month follow-up period on groups with previously known and unknown caffeine impact. Method: We created a direct-to-consumer approach, that includes providing relevant information, personalized reminders, and goals on the digital device regarding the caffeine intake for two groups of individuals. The intervention group/IG with the genetic raw data available and to test the impact of the same content (article about caffeine metabolism) on participants without the genetic test, control group/CG. Study participants were all Estonians (n=160). Results: The study suggests that eHealth applications work for short-term behavior change. Participants in the genetic intervention group tended to increase caffeine intake if they were confirmed about caffeine not being harmful. They reported feeling better physically and/or mentally after their behavioral change decision during the period of the study. Conclusions: Our pilot study revealed that eHealth applications may have a positive effect on short-term behavior change, regardless of a prior genetic test. Further studies among larger study groups are required to achieve a better understanding of the behavior change of individuals in the field of personalized medicine and eHealth interventions.